Indirect regulation of topsoil nutrient cycling by groundwater depth: impacts on sand-fixing vegetation and rhizosphere bacterial communities - Hao, Lianyi; Liu, Xiuhua; Ji, Ruiqing; Ma, Yandong; Wu, Puxia; Cao, Qingxi; Xin, Yunling (Frontiers in Microbiology, 2023)
nutrient availability correlated with keystone bacteria, and changes in nitrogen content could be attributed to nitrogen mineralization. This indicates that fluctuations in the groundwater table play a role in regulating microbes and the distribution of soil carbon and nitrogen nutrients in arid environments. Consequently, maintaining a GTD within a reasonable range is imperative for ecological restoration in arid regions. Preserving an appropriate ecological groundwater depth is essential to mitigate sandy vegetation degradation and enhance soil fertility accumulation.